Turkey’s Reasons to Normalize Diplomatic Relations with Israel in 2021 - Isyfa Zahrotul Mufidah; Haryo Prasodjo; Najamuddin Khairur Rijal; Havidz Ageng Prakoso (Journal of Islamic World and Politics, 2022)
This article discusses the reasons for Turkey's normalization with Israel in 2021. Diplomatic relations between the two sides have been established for more than 70 years since the state of Israel was founded, although the dynamics of their relationship have experienced ups and downs. This study is qualitative research in which the analysis of this phenomenon is taken from news reference sources, articles, reports and documents, using the theory of Foreign Policy Analysis by Valerie M.Hudson. The results of this analysis show that three important aspects make Turkey carry out normalization with Israel, first from an economic perspective which is the main aspect of normalization, second from a political aspect and finally from a security or military perspective. Israel has become Turkey's strategic partner even though as an Islamic country that carries out normalization with the Jewish state, this is a strategy that Turkey wants to build, because this policy it is the foundation for achieving national interests.